2020
DOI: 10.3389/fmed.2020.00161
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Sequencing and Spatial Analysis Identifies Recent Tuberculosis Transmission Hotspots in Ghana

Abstract: Whole genome sequencing (WGS) is progressively being used to investigate the transmission dynamics of Mycobacterium tuberculosis complex (MTBC). We used WGS analysis to resolve traditional genotype clusters and explored the spatial distribution of confirmed recent transmission clusters. Bacterial genomes from a total of 452 MTBC isolates belonging to large traditional clusters from a population-based study spanning July 2012 and December 2015 were obtained through short read next-generation sequencing using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 47 publications
3
12
0
Order By: Relevance
“…These two samples respectively showed high and medium bacterial load when analyzed with GeneXpert MTB/RIF assay indicating that there could be a high chance of community spread of TB with such high bacterial loads detected [ 16 ]. Interestingly, these two TB positive samples from contact tracing were both from the Ayawaso sub-district which our previous studies have confirmed to be a hotspot for active TB transmission [ 17 ].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These two samples respectively showed high and medium bacterial load when analyzed with GeneXpert MTB/RIF assay indicating that there could be a high chance of community spread of TB with such high bacterial loads detected [ 16 ]. Interestingly, these two TB positive samples from contact tracing were both from the Ayawaso sub-district which our previous studies have confirmed to be a hotspot for active TB transmission [ 17 ].…”
Section: Discussionmentioning
confidence: 90%
“…This further stresses the need to conduct frequent community screening of individuals in known hotspot communities such as Ayawaso and Ablekuma sub-districts where active TB transmission has been shown to be taking place [ 17 ]. There is therefore the need for active community case search to ensure early active TB case detection to ensure efficient management to cut any potential spread.…”
Section: Discussionmentioning
confidence: 99%
“…Whole Genome Sequencing (WGS) is useful in the detection of unsuspected outbreaks; therefore, it is a useful research tool and can also be part of surveillance programs to help in the tracking, monitoring, and control of TB. It also aids in the recognition of MTB strains associated with drug resistance and in the identification of hotspots [ 52 ]. Co-existence of two or more strains of mycobacteria may present with a complex challenge of misidentification of MTB.…”
Section: Genetic Aspects Of Tbmentioning
confidence: 99%
“…Despite some reports indicating the reduced fitness as a result of drug resistance evolution [ 20 , 21 ], others have indicated emanating high fitness strains with preserved ability to spread [ 22 , 23 ]. Thus, the latter might explain the scenario in our current study.…”
Section: Discussionmentioning
confidence: 99%